Evidenciando uma arte antiga da praia do Mucuripe: a contribuição da cadeia produtiva da pesca artesanal para o desenvolvimento sustentável - Costa, Gerliane Maia (2022)
The present research proposes to analyze the contribution of the artisanal fishing production chain in the Mucuripe cove for economic, social and environmental sustainability. The research is based on the theory of the productive chain. The unit of analysis was the Mucuripe cove, located in the Coastal Zone of Fortaleza, as it is the main artisanal fishing point in the capital. The period analyzed was the year 2021. Data were collected through primary sources, with 15 valid questionnaires and 5 semi-structured interviews. To achieve the proposed objectives, the methods that best suited the research needs were used as a basis for each of the analyses, namely: for the economic analysis, the effects method; for social analysis, the social profile; and for the environmental analysis, the ecological dimension of the RAPFISH method. In the case of functional analysis, it helps to characterize the chain. The results indicate that the production chain of artisanal fishing in the Mucuripe cove starts with pre-harvesting (acquisition of inputs), followed by capture (fish production) and ends with post-harvesting (1st sale, processing, 2nd sale and end consumers). This production chain comprises two sub-chains, the lobster and the fish, which have different destinations in the post-harvest. Given the complexity of collecting data for all agents in the chain, the present research, when carrying out economic, social and environmental analyses, was limited to the production stage, until the first sale. As for the economic analysis, it was identified that the actors are obtaining revenue and creating added value, in which, from the data, a total added value of R$ 38,049,595.59 was estimated.This value represents 0.06% of Fortaleza's Gross Domestic Product (GDP) and 44.37% of agricultural GDP. In addition, they are generating income, a trade balance surplus, and despite not contributing directly to public finances, the total contribution rate was 2.40%, indicating a transfer to public coffers. Thus, it is understood that the production stage of the studied chain is economically sustainable. The social profile values, on the other hand, had scores between 2 and 3 points, with the exception of the gender equality indicator, which had a score of 1, as there are no women in the artisanal fishing of the Mucuripe cove. From the data and scores of the indicators, it is understood that the production stage is not socially sustainable. Finally, when carrying out the environmental analysis of the production stage, it was identified that it is not environmentally sustainable in all aspects. Because, of the 8 attributes analyzed, 5 of them presented medium and high percentages.